THE EFFECTS OF PROBIOTICS ON DRINKING WATER AGAINST ABDOMINAL FAT DISTRIBUTION OF FEMALE DUCKS - Anjarwati, A.; Mudita, I M.; Sutama, I N. S. (Jurnal Peternakan Tropika; Vol 9 No 2 (2021): Vol. 9 No. 2 Tahun 2021; May - August, 2021)
The research which aims to determine the effect of probiotics through drinking water on the distribution of female ducks' abdominal fat has been conducted at the Sesetan Laboratory, Faculty of Animal Husbandry, Udayana University for 8 weeks. The design used was a completely randomized design (CRD) consisting of three treatments, namely: ducks that were given drinking water without probiotics as a control (A), ducks that were given drinking water + 2.5 ml of probiotics (B), ducks that were given drinking water + 5 ml of probiotic (C). Each treatment consisted of five replications and each replication used three Balinese female ducks aged 3 days with average weight. The observed variables were weight and percentage of bearing fat, weight and percentage of mesentrial fat, weight and percentage of bile fat, and weight. and percentage of abdominal fat. The results showed that the combination of probiotic bacteria Bacillus subtillis strains BR2CL and Bacillus sp strain BT3CL through drinking water as much as 2.5 ml / head / day was not able to affect the distribution of abdominal fat for female bali ducks aged 8 weeks, but giving probiotics as much as 5 ml / head. / day resulted in an increase in weight bearing fat (pad fat) and weight of bile fat (ventriculus fat), but did not affect other abdominal fat variables. Keywords: Probiotics, female Bali ducks, abdominal fat distribution.